Myocardial performance index for detection of subclinical abnormalities in patients with sarcoidosis - Kaya, Mehmet Gungor (Pioneer Bioscience Publishing Company, 2014)
AIM: The aim of this study was to evaluate ventricular functions in patients with sarcoidosis without an obvious heart disease by using tissue Doppler-derived left and right ventricular myocardial performance index (MPI). METHODS: The study population included 45 patient with sarcoidosis (29 men, 16 women; mean age, 44±10 years, mean disease duration, 4.2±2.7 years) and 45 healthy control subjects (31 men, 14 women; mean age, 41±8 years). Cardiac functions were determined using echocardiography, consisting of standard two-dimensional and conventional Doppler and tissue Doppler imaging (TDI). Myocardial tissue Doppler velocities [peak systolic (Sa), early diastolic (Ea), and late diastolic velocities (Aa)] were recorded using spectral pulsed Doppler from the LV free wall, septum, and RV free wall from the apical four chamber view. MPI was also calculated by TDI. RESULTS: The conventional echocardiographic parameters and tissue Doppler measurements were similar between the patients and controls. Left ventricular MPI (0.490±0.092 vs. 0.396±0.088, P=0.010) and right ventricular MPI (0.482±0.132 vs. 0.368±0.090, P=0.006) were significantly higher in patients with sarcoidosis than the control subjects. There was a correlation between the disease duration and right and left ventricular MPI (r=0.418, P=0.005; r=0.366, P=0.013, respectively). There was also a correlation between the systolic pulmonary arterial pressure and right ventricular MPI but not left ventricular MPI (r=0.370, P=0.012; r=0.248, P=0.109, respectively). In receiver operating characteristics curve analysis, the cutoff value of left ventricular MPI >0.46 had 92% sensitivity and 64% specificity in predicting left ventricular diastolic dysfunction. CONCLUSIONS: We have demonstrated that tissue Doppler-derived myocardial left and right ventricular MPI were impaired in sarcoidosis patients, although systolic function parameters were comparable in the patients and controls, showed a subclinic impaired ventricular functions in patients with sarcoidosis.